Dukungan Suami Terhadap Penggunaan IUD Pasca Plasenta Sebagai Kontrasepsi Pasca Melahirkan - Wafi Nur Muslihatun; Ana Kurniati; Dian Maliana; Juli Widiyanto (Sistem Informasi, 2021)
Postplacental IUD is a post-partum contraceptive device that can be inserted directly in the first 10 minutes after the placenta is born. The low interest in post-placental IUD use is strongly influenced by husband's support. This study aims to determine the relationship between husband's support and the use of the postplacental IUD as a post-delivery family planning program. This type of research is analytic observational with a cross sectional approach. The sample of this study was 62 mothers giving birth at the Pratama Clinic Kusuma Medisca Wates taken by simple random sampling technique. The research instrument used a husband's support questionnaire. Data analysis was performed by Chi Square test. Maternal mothers who used the postplacenta IUD were more mothers who received husband's support (40.3%) compared to mothers who did not receive husband's support. Statistical test results obtained p-value 0.000, prevalence rate 5.26 with a confidence interval range of 0.064-0.561. Conclusion: There is a significant relationship between husband's support and the use of the postplacental IUD as a postpartum contraception.